Stategic Service Analysis to Enhance Occupancy Rate of Ganesha Public Speaking School by Increasing Awareness to The Targeted Segment (The Indonesian Journal of Business Administration, 2013)
GPSS suffered from its low occupancy rate, which is equal to 12%. This figure is still far from the company’s target which is 70%. Using Company, Industry and Targeted Customer Analysis, the business solutions will be proposed by considering the lowest possible cost, yet provides the bigest possible results. The data used are primary data which consist of company’s internal data and questionnaires. Based on those analyses, there are three issues that need consideration the most are: the marketing issue, office issue and trainer issue. The proposed business solution will require Rp 19 million for year 2013. Keywords: Service, Occupancy rate, Public Speaking Training, Segmenting, Clustering, Awareness.